A case of pulmonary aspergillosis masquerading as pulmonary tuberculosis in a patient with type 2 diabetes mellitus - Sidharth Shankar Panigrahi; Jayshree Swain; Vejendla S Srinivas; K. Lavanya; Teli Brij Rajesh (Journal of Krishna Institute of Medical Sciences University)
Patients with diabetes are more susceptible to infections than non-diabetics and often have severe clinical manifestations. The underlying immune dysregulations in these patients result in them developing serious, life-threatening infections. Pulmonary tuberculosis is a common respiratory infection seen in diabetics in India. However, there are certain rare yet life-threatening infections that can mimic pulmonary tuberculosis, like pulmonary aspergillosis. Pulmonary aspergillosis is seen in various immunocompromised patients. Rarely, it is also seen in diabetics with poor glycemic status. We present a case of pulmonary aspergillosis in a patient with type 2 diabetes who was undergoing treatment for pulmonary tuberculosis. His symptoms persisted despite anti tubercular therapy. Based on High Resolution Computed Tomography (HRCT) findings and the galactomannan assay in BAL fluid, patient was diagnosed to have probable pulmonary aspergillosis. He was started on anti-fungal therapy with subsequent improvement in his signs and symptoms. This case highlights the importance of considering fungal infections as an important differential in patients with diabetes with relevant pulmonary findings.